Utilization of Green Bean Extract for Pregnant Women with Anemia at the Limboto Health Center, Limboto District, Gorontalo Regency - Ani Retni; Harismayanti Harismayanti (Journal of Universal Community Empowerment Provision, 2022)
Carrying out service with the theme of Utilizing Green Bean Extract for Anemia in Pregnant Women. carried out on pregnant women in the Limboto Health Center Work Area, Limboto district, Gorontalo Regency. For pregnant women, the nutritional content of green beans can be useful in preventing anemia. Iron is one of the minerals that has an important role in the formation of red blood cells. However, nuts usually contain phytic acid which binds minerals so they cannot be absorbed optimally. The process of soaking, cooking, and germination can reduce the content of this phytic acid and increase the digestible iron. The purpose of this activity in general is to improve the degree of public health through increasing knowledge of pregnant women about the use of mung bean juice for anemic pregnant women. Demonstrating the Steps of Making Green Bean Juice